2000
DOI: 10.1016/s0960-9822(00)00473-5
|View full text |Cite
|
Sign up to set email alerts
|

The guanine nucleotide exchange factor CNrasGEF activates Ras in response to cAMP and cGMP

Abstract: Small GTPase proteins such as Ras are key regulators of cellular proliferation and are activated by guanine nucleotide exchange/releasing factors (GEFs/GRFs). Three classes of Ras GRFs have been identified to date, represented by Sos1/2, Ras-GRF1/2 and Ras-GRP. Here, we describe a novel candidate Ras activator, cyclic nucleotide rasGEF (CNrasGEF), which contains CDC25, Ras exchange motif (REM), Ras-association (RA), PDZ and cNMP (cAMP/cGMP) binding (cNMP-BD) domains, two PY motifs and a carboxy-terminal SxV se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
121
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 14 publications
5
121
1
Order By: Relevance
“…It has been shown that all three post-translational modi®cations of Rap 1 are necessary for full activation of Rap 1 by smg GDS and because cyclic nucleotides did not activate Rap 1 in the variant cells, our data suggest that full post-translational modi®ca-tion of Rap 1 may be necessary for the action of cAMP-GEFs on Rap 1. Whether the activation of Rap 1 by 8-pCPT-cGMP occurred through crossactivation of one of the identi®ed cAMP-GEFs (De Rooij et al, 1998;Kawasaki et al, 1998;Pham et al, 2000) or through a novel cGMP-binding RapGEF is under investigation. Further study of the variant cells should help to provide information about the role of Rap 1A in cellular signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that all three post-translational modi®cations of Rap 1 are necessary for full activation of Rap 1 by smg GDS and because cyclic nucleotides did not activate Rap 1 in the variant cells, our data suggest that full post-translational modi®ca-tion of Rap 1 may be necessary for the action of cAMP-GEFs on Rap 1. Whether the activation of Rap 1 by 8-pCPT-cGMP occurred through crossactivation of one of the identi®ed cAMP-GEFs (De Rooij et al, 1998;Kawasaki et al, 1998;Pham et al, 2000) or through a novel cGMP-binding RapGEF is under investigation. Further study of the variant cells should help to provide information about the role of Rap 1A in cellular signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For cGMP to function, it must bind to and regulate the activity of key proteins. In metazoans cGMP signaling is mediated by cGMP-dependent protein kinases (PKGs), cGMP-gated ion channels, a cAMP͞cGMP-regulated RasGEF (6), and cGMP-regulated phosphodiesterases (PDEs). The cGMP-binding sites in these proteins are homologous to the Escherichia coli catabolite gene activator protein (CAP), except for the PDEs, which bind cGMP by using GAF domains (cGMPspecific and stimulated PDEs, Anabaena adenylate cyclases, and E. coli FhlA; ref.…”
mentioning
confidence: 99%
“…In our search for such putative targets, we had performed an expression screen of 16-day-old mouse embryo library with the second Nedd4-WW domain as a probe. This screen resulted in the isolation of a C-terminal fragment of the cyclic nucleotide Ras GEF (CNrasGEF (6); also known as KIAA0313, nRap-GEF1, PDZ-GEF1, and RA-GEF (7)(8)(9)). …”
mentioning
confidence: 99%
“…It has several domains and motifs, including a cyclic nucleotide (cAMP/cGMP)-binding domain (cNMP-BD), Ras exchange motif, PDZ domain, Ras association domain, a CDC25 domain similar to that of Sos1/2, GRF1/2, GRP, as well as Rap GEFs such as Epac, two PY motifs (PPGY and PPDY, see Fig. 1A) and a C-terminal SAV sequence conforming to a PDZ binding motif (6). Ras proteins play a key role in controlling many cellular processes, including proliferation, differentiation, and apoptosis (10 -12).…”
mentioning
confidence: 99%